2010
DOI: 10.1111/j.1471-0307.2010.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of breed on the organoleptic characteristics of Zamorano sheep’s raw milk cheese and its assessment by instrumental analysis

Abstract: The aim of this study was to investigate the effects of three different somatic cell count (SCC) values on the sensory characteristics of sheep’s milk cheeses from the Castellana and Churra breeds (allowed for Protected Designation of Origin Zamorano cheese manufacture) and the Assaf breed (foreign), determined by typical consumers and instrumentally. The results show that the sensory characteristics of hardness, intensity of taste, and pungency reflect a significant influence of the SCCs of the original milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…Nonetheless, proteolytic and lipolytic activities are inherent to the cheese maturation process, and after several months it may be difficult to distinguish the SCC and the effects of time. In fact there were no significant differences in the percentage of proteolysis or chemical composition up until the sixth month of maturation, although higher fat acidity and higher pH was observed in high SCC milk cheeses (Jaeggi et al, 2003;Revilla et al, 2007Revilla et al, , 2011 and some textural and flavor defects were reported after 12 mo of ripening (Lurueña-Martínez et al, 2010b). Despite the relevance of the SCC on cheese quality, no data regarding cheese classification according to this factor have been found.…”
Section: Introductionmentioning
confidence: 88%
“…Nonetheless, proteolytic and lipolytic activities are inherent to the cheese maturation process, and after several months it may be difficult to distinguish the SCC and the effects of time. In fact there were no significant differences in the percentage of proteolysis or chemical composition up until the sixth month of maturation, although higher fat acidity and higher pH was observed in high SCC milk cheeses (Jaeggi et al, 2003;Revilla et al, 2007Revilla et al, , 2011 and some textural and flavor defects were reported after 12 mo of ripening (Lurueña-Martínez et al, 2010b). Despite the relevance of the SCC on cheese quality, no data regarding cheese classification according to this factor have been found.…”
Section: Introductionmentioning
confidence: 88%
“…Identity and Quality of Cheeses (BRASIL, 1996). This regulation classifies Prato cheese as a fat cheese, which must present 45 to 59.9% fat in dry matter (F/DM) and mean values of moisture varying from 36 to 45.9%.…”
Section: Color Stabilitymentioning
confidence: 99%
“…The Assaf milk yield (400 kg) is more than double of the milk yield in Churra (117 kg), although Assaf milk has lower fat (6.65 vs. 7.01) and protein content (5.40 vs. 5.79) ( http://www.magrama.gob.es/es/ ). Hence, Churra milk shows better mature cheese-making yield and organoleptic properties 6 .…”
mentioning
confidence: 99%